Are we in the same boat?: Value-creation in alliance portfolios in the US internet sector - Kim, Kimin (International Journal of Economics and Business Research, 2020)
Current research admits that value-creation occurs between the focal firm and its partner firms in alliance portfolios. However, most extant studies have focused on performance implications from the perspective of the focal firm. We consider the partner firms' perspective in examining the relationship between portfolio configuration and stock market valuation, along with the moderating role of environmental munificence. Using data on the alliance portfolios of 120 focal firms in the US internet sector covering 1995 to 2003, we found that partner firms that ally with a focal firm with higher portfolio diversity and/or higher portfolio density are likely to enjoy greater abnormal returns when the focal firm announces corporate events. We also found that portfolio density is more likely to be associated with higher abnormal returns when environmental munificence is low than when it is high.
Keywords: Alliance portfolio; Environmental munificence; Portfolio configuration; Strategic alliance network